Accounting for derivatives and hedging activities - Beil, Frank J., (2013 digital library., 2013)
Derivatives, and derivatives used to hedge financial and operating functions, are designed to allow managers of firms to manage effectively the downside risk of their financial and operating strategies. They also can be very useful tools that allow managers and executives to accurately predict financial and operational performance and manage the investment communities expectations regarding overall firm performance. Derivatives and hedges, however, if not properly designed in conjunction with the firm's risk management strategy, can be potentially disastrous for the firm. The ongoing financial turmoil in markets can be partially explained by company managers and executives not understanding the potential financial statement impact when derivative markets move in a particular direction for longer periods of time than anticipated by firms.